1990
DOI: 10.1002/app.1990.070390308
|View full text |Cite
|
Sign up to set email alerts
|

High performance size‐exclusion chromatography of anionic polymers in aqueous solutions

Abstract: SynopsisThe applicability of high performance size-exclusion chromatography was tested for anionic polymers with a new type of column. It was found that a solvent salt concentration of 0.1M and an elevated temperature (60°C) prevented adsorption of the polystyrene sulfonate standards on the column packing. The calibration curve and the effect of the concentration on the retention volume remained, however, column-dependent. We concluded also that the use of the column was restricted to the linear range of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…In addition, their mean MN was 245 kDa, and their mean MW was 530 kDa. These average molecular weight values were similar to those reported previously by some authors (Ekstrom 1985, Lecacheux et al 1985, Malfait et al 1990, Slootmaekers et al 1991.…”
Section: Average Molecular Weights Of Carrageenanssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, their mean MN was 245 kDa, and their mean MW was 530 kDa. These average molecular weight values were similar to those reported previously by some authors (Ekstrom 1985, Lecacheux et al 1985, Malfait et al 1990, Slootmaekers et al 1991.…”
Section: Average Molecular Weights Of Carrageenanssupporting
confidence: 92%
“…Ekstrom (1985) tested eight samples of food-grade -carrageenan by using the system of GPC and the refractive index (RI) detector, and found the mean value of weight average molecular weights (MW) of these carrageenans was 167 kDa. Malfait et al (1990) reported that the MW of carrageenan was 303 kDa by using a similar system and that a broad peak of carrageenan was followed by a low molecular weight fraction. Lecacheux et al (1985) tried to use low angle laser light scattering (LALLS) as a detector.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the logarithms of the M p values determined by MALDI-MS were plotted as function of the corresponding retention volume ratios ( K ) obtained from the SEC separation (Figure ). These K values represent the ratio between the elution volume for a given hemicellulose and the elution volume for DMSO (used as the flow marker), according to the approach suggested by Malfait et al Calculation of the K value in this manner compensates for variations in the elution volume of a hemicellulose in connection with different SEC separations, which arise primarily from variations in flow rate.
6 Relationship between log M p (determined by MALDI-MS) and the relative retention volume ( K ) obtained with SEC for different hemicelluloses eluted with ammonium acetate or sodium hydroxide/acetate.
…”
Section: Resultsmentioning
confidence: 99%